Vivenciar aprendendo: contribuições da pedagogia Waldorf à formação do pedagogo no século XXI - Cruz, Denise Santos da (2017)
This Master's thesis, developed in the Postgraduate Program in Education of the Federal University of Santa Maria (UFSM), Research Line 1 (LP1) - Training, knowledge and professional development, has as its central theme the formation of the educator in the context of Waldorf pedagogy (pW) and the contributions to the formation of the pedagogue today. The peculiarities of the formative processes differentiate it from the traditional formation, bringing elements that could mean new paradigm in the formation of teachers, mostly for the Basic Education. It is a qualitative research of narrative approach, aiming at the understanding of the meaning of "becoming a Waldorf educator", therefore it was decided to approach with a context of formation, the Waldorf Pedagogy Practices Class and educators in formation, some of whom contributed with their formative memorials, that is, their "experiencing learning", making them subjects / personages, including the author of this dissertation, also participant of the class. In the constitution of the essay are the systematic review of the literature and formation memorials, making it possible to compare contributions to the education of the pedagogue nowadays.They are: (1) Rudolf Steiner developed the pW from educational experiences and relevant to the formation of the human being and to anthroposophic ideas, which have man at the center of his ethical and educational concern - the truly free man; (2) It establishes an educational proposal that is continually renewed, following the advances of humanity and respecting the knowledge of the communities where it is inserted; (3)The pW has great consideration for the self-education of the teacher, seen as a permanent process of learning; the first group of Waldorf educators experienced their learning mediated by Steiner himself in the conduct of his living and experiences; (4) The healthy and enduring relationship of the teacher-student in the pW is a pedagogical premise, since the teacher will be a tutor to accompany his students from the moment they enter the institution until they leave school (around eight years), generating a bond of love and confidence, qualifying the formation; (5) The evaluation of students is procedural and qualitative, starting from the different aspects of the life of the student as a human being; (6) Coherently, the development of the students is characterized in seven-year periods, considering pedagogically the needs of each phase in the appreciation of the self, of the other and of the world. In the first seven years (0-7 years), "the world is good." In the second seventh (7-14 years), "the world is beautiful" and in the third (14-21 years), "the world is true"; (7) The Waldorf Schools are constituted of supporting associations, generally supported by sympathizers, parents, teachers and persons connected to Anthroposophy, participating voluntarily, without remuneration. The functions of the school are remunerated through the budget of the monthly fees; (8) The pedagogical activities are developed in the theory/practice articulation permeated by the arts, cultures and languages within the context of the movement as a basis in human life and (9) Understanding the Digital Culture and its implications in the formative process of the new generations, the pW guides the educators (teachers, parents, caregivers ...) to the wisdom of digital media. It is recommended to use digital technological resources only from high school, assuming that at this stage the user has self-control over his actions, knowledge and insight to use a digital device that gives access to information indiscriminately. The pW guides children and young people towards the development of their autonomy in the face of influences of harmful contents to health as integrality of feeling, thinking, acting and wanting. It is considered that the objectives of the dissertation led the study, allowing the experience to learn from the author in order to integrate the learned in her own experience of "becoming a Waldorf educator", undoubtedly an incomplete task, since it will be a movement for all life, in all its dimensions.